Board games round the world : A resource book for mathematical investigations - Bell, Robbie; Cornelius, Michael (New York : New Rochelle : Cambridge University press, 1988)
Mathematicians as well as games enthusiasts will appreciate the nearly sixty international board games described in this informative work on the history and rules of the world's oldest form of universal amusement. The types of games and individual games included offer classroom tested opportunities for the application of various mathematical methods and strategies.
Includes bibliographical references.
Keywords: Board games; Games in mathematics education; Educational games